Nonsyndromic hemimandibular hypoplasia: A case report with a short review of the literature - Sourav Bhattacharya; Dibyendu Mazumder; Debarati Ray; Sumit Ray (Wolters Kluwer Medknow Publications, 2015)
Mandibular hypoplasia (MH) is a condition, which characterizes deviation in the mandibular growth patterns causing functional and esthetic alterations. MHs encountered in the craniofacial region may be of three types: Congenital, developmental and acquired. Majority of the MHs are associated with syndromes with very little emphasis on the "nonsyndromic" category. Furthermore, the hypoplasias generally have a bilateral manifestation on the mandible. We focus on the nonsyndromic category and report a case of isolated unilateral MH in a 17-year-old boy with obvious facial disfigurement but with no association to any syndrome. The objective of this presentation is to highlight the rarity, possible manifestations and diagnostic approach of the nonsyndromic group.